Port Revenue Performance and Economic Growth: The Nigerian Ports Authority Experience, 2010-2019 - Osadume Richard C.; University Edih O. (Logi, 2020)
The Study examined Port Revenue Performance and Economic Growth: The Nigerian Ports Authority Experience, 2010 to 2019. The objective of this study is to examine the effect of Port Revenue Performance on Nigeria's economic growth by critically evaluating the Nigerian Ports Authority Performance. The neoclassical growth theory was employed in the study and the Nigeria Ports Authority was chosen as its sample, covering the period from 2010 to 2019. The study used secondary time series data sourced from the Nigeria Ports Authority and the National Bureau of Statistics and used the ordinary least square regression and the Engle-Granger co-integration to test the variables at the 5% level of significance. The findings showed that total revenue to gross registered tonnage had positive and significant effect on economic growth while operating surplus to operating revenue showed a negative but significant effect and operating surplus to cargo throughput showed insignificant effect; there was no co-integration between the variables. The study concludes that Port revenue performance affects economic growth in the short-run only, and it recommends amongst others that policy makers should formulate appropriate and implementable regulatory framework that will address infrastructural deficits at the ports and stimulate increased utilization by major foreign vessel companies.